La dramatización en la competencia se comunica oralmente en su lengua materna en estudiantes de tercer grado de primaria - Vilchez Castañeda, Mayra Elizabeth (2023)
The objective of this work was to improve the oral communication competence in their mother tongue in third grade "C" students of the institution xx, through dramatization, in which the representation of fables will take place. Therefore, the four processes of dramatization were taken into account: preparation and creative process, realization and critical evaluation; achieving that the students are encouraged to represent the fables using communicative skills such as active listening, empathy, among others to communicate ideas learned from the readings of the fables, as well as using their body through gestures, mimics to convey emotions of the characters they represent. All the above mentioned under a climate of respect, trust and mutual support. The pedagogical current that sustains the methodology is constructivist, in which various theories are found, among which the following stand out: sociocultural theory, cognitivist theory, and meaningful learning. Hence, it was concluded that the dramatization strategy contributed adequately to the improvement of oral expression, since the students pronounced and intoned the words and phrases adequately according to the character to be interpreted, managing to transmit emotions and teachings.